IDENTIFIKASI SENYAWA METABOLIT SEKUNDER DALAM EKSTRAK BIJI KELOR (MORINGA OLEIFERA L) YANG BERPOTENSI SEBAGAI ANTIOKSIDAN - Julianus Dising; Paulus Pasau (Partner, 2022)
The study aimed to identify and determine the total levels of secondary metabolite compounds from moringa seed extracts that have the potential to be antioxidants. Moringa seeds used in this study came from Kupang Regency and Kupang City, East Nusa Tenggara. Moringa seeds are extracted using a 96% ethanol solvent by the maceration method for 48 hours. After that, it is filtered and the filtra is separated between the solvent and the alcohol extract (moringa seed extract) using rotary evaporator (rotavapour). Moringa seed extract was obtained subsequently and analyzed qualitatively and quantitatively to identify and find out the levels of its secondary metabolites (flavonoids, saponins, alkaloids, and tannins). The results showed that based on qualitative and quantitative analysis, moringa seed extract contained flavonoid compounds (0.763%), saponins (6,185%), alkaloids (918,782 ?g/g), and tannins (3.814,193 ?g/g). These secondary metabolite compounds have the potential to be antioxidants.Keywords: secondary metabolites, moringa seeds, antioxidants, maceration